Inventory Management Assistance in "Rayyan Gallery" Business - Liyundira, Fetri Setyo (IMPOWERMENT SOCIETY, 2021)
Trading companies are supplied by way of purchase of finished goods ready for sale back directly. While manufacturing companies get supplies by way of their own manufacture. So that manufacturing companies will incur production costs such as raw material costs, direct labor costs, and factory overhead costs. In the FIFO method, the value of goods that will go out for production activities is based on the price that was first entered. So that the final goods inventory using a price based on the new price or the price with the last order purchased. Therefore, the FIFO method is more visible for calculating the COGS . The cost used to purchase the first item is the Cost Of Good Sold (COGS). The selling price calculation is based on the price of the previous transaction stock of goods. The availability of sufficient and quality information will make it easier and faster for management to make decisions, it is necessary to distribute computerized information so that the information provided is more accurate, efficient and effective in realizing the goals of the company when compared to manual data processing. By creating an application program that uses Visual Basic 6.0 programming will help in systemized data processing.